DESAIN IMPLEMENTASI PENYELENGGARAAN PEMERINTAHAN DESA BERDASARKAN UU NO. 6 TAHUN 2014 TENTANG DESA DI KABUPATEN SEMARANG - Kushandajani Kushandajani (Politika: Jurnal Ilmu Politik, 2015)
This research is motivated by the deepen concern toward  the fenomena of Desa  in Indonesia, in otherhand application of desa regulation through the law No.  6 of 2015  is exist for a while. So, it’s important thing to study how the law No.6 of 2015 makes design to execute  governance in Desa. Result this research describes that central government and local government are not ready to implement UU No. 6 of 2015. Local government of Kabupaten Semarang still have  one local regulation of Kepala Desa election, three planned local regulations of desa’s finance, desa’s social organization, and desa’s government. There are three Peraturan Bupati of desa’s finance, management of desa’s finance, and desa’s government staff payment. . Keywords: village governance, village authority, village original rights, village  government functions, village based local authority